Pengaruh Customer Relationship Marketing Terhadap Customer Loyalty Melalui Customer Value Pada Bank Jatim Di Jember - Diah Yulisetiarini; Rizal Syahrial Riadi; Gusti Ayu Wulandari (e-Journal Ekonomi Bisnis dan Akuntansi, 2017)
This research is aimed to analyse the influence of customer relationship marketing and customer value to customer loyalty in Bank Jatim Jember. This reserach using explanatory research aproach, the population are those customers who of bank jatim jember with obtained 110 respondents as sample using ferdinand formulas .The analyse method in this research using path analyse .The result of this research is customer relationship marketing significantly influenced customer value, customer relationship marketing significantly influenced customer loyalty, customer value significantly influenced customer loyalty . Keywords: Instability of exports, instability indexes, non-oil, export